The digital photography book. Part 1 : the step-by-step secrets for how to make your photos look like the pros'! - Kelby, Scott (2013)
Furnishes an overview of digital photography, covering such topics as cameras, exposure, lighting, shutter speed, depth of field, and resolution--and tips on how to avoid hours of photo-editing by taking great photographs the first time.
Pro tips for getting really sharp photos -- Shooting flowers like a pro -- Shooting weddings like a pro -- Shooting landscapes like a pro -- Shooting sports like a pro -- Shooting people like a pro -- Avoiding problems like a pro -- Taking advantage of digital like a pro -- Taking travel & city life shots like a pro -- How to print like a pro and other cool stuff -- Ten things I wish someone had told me -- Photo recipes to help you "get the shot".
Previous ed.: 2006.
Includes index.
Keywords: Photography -- Digital techniques